ASSESSMENT OF YORUBA LANGUAGE CURRICULUM IMPLEMENTATION IN LOWER PRIMARY SCHOOLS IN OSUN STATE, NIGERIA - Sosan, Ibidun Asisat; Okewole, Johnson Oludele (The University of Kuningan, 2024)
There is notable inadequacy in the amount of Yoruba Language content being offered to learners, which could impede their self-sufficiency. It thus appears that the methods and instructional materials stipulated for Yoruba Language Curriculum are not adequately used to impart knowledge to the pupils. This study, therefore, examined the qualifications of teachers teaching Yoruba Language in lower primary schools in Osun State; assessed the availability and usage of instructional materials in teaching Yoruba Language in the lower primary schools and ascertained the appropriateness of the methods being used as stipulated in the Yoruba Language curriculum in the study area. These were with a view to providing empirical information on the quality of teachers teaching Yoruba Language, the availability as well as usage of instructional materials and the appropriateness of the methods being used at the lower primary schools in Osun State. The study employed a descriptive survey research design. Three research instruments were employed in this study namely Yoruba Language Teachers’ Questionnaire (YLTQ), Yoruba Language Instructional Material Checklist (YLIMC) and Yoruba Language Teaching Method Observation Checklist (YLTMOC). Data collected were analyzed using percentages and frequency counts. The results showed that majority (62.8%) of the Yoruba Language teachers possessed Nigerian Grade II Teachers Certificate and the National Certificate of Education (NCE) as their educational qualifications. The findings of the study also showed that most of the instructional materials that were available in the schools were not adequately used by the teachers teaching Yoruba Language in the study area The study further revealed that methods used in majority of the schools are appropriate as prescribed by the National Policy on Education (2013).Keywords: Yoruba Language; curriculum; lower primary; instructional resources